2017
DOI: 10.1002/2016jb013183
|View full text |Cite
|
Sign up to set email alerts
|

Experiments versus theory for the initiation and propagation of radial hydraulic fractures in low‐permeability materials

Abstract: We compare numerical predictions of the initiation and propagation of radial fluid‐driven fractures with laboratory experiments performed in different low‐permeability materials (PMMA, cement). In particular, we choose experiments where the time evolution of several quantities (fracture width, radius, and wellbore pressure) was accurately measured and for which the material and injection parameters were known precisely. Via a dimensional analysis, we discuss in detail the different physical phenomena governing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 49 publications
(82 reference statements)
7
63
0
Order By: Relevance
“…Each of these studies found a linear increase in breakdown pressure with confining pressure, and rapid, uncontrolled breakdown once the peak injection pressure was reached. Zoback et al (1977), Bunger and Detournay (2008), Stanchits et al (2015), and Lecampion et al (2017) found that for experiments injecting higher-viscosity fluids, the breakdown pressure can be higher than the fracture initiation pressure, in agreement with the models summarized by Detournay (2016).…”
Section: Laboratory-scale Fluid Injection Experimentssupporting
confidence: 62%
“…Each of these studies found a linear increase in breakdown pressure with confining pressure, and rapid, uncontrolled breakdown once the peak injection pressure was reached. Zoback et al (1977), Bunger and Detournay (2008), Stanchits et al (2015), and Lecampion et al (2017) found that for experiments injecting higher-viscosity fluids, the breakdown pressure can be higher than the fracture initiation pressure, in agreement with the models summarized by Detournay (2016).…”
Section: Laboratory-scale Fluid Injection Experimentssupporting
confidence: 62%
“…It is also important to note that the compressibility of gas or supercritical CO 2 may effect early‐time crack propagation. However, for the intermediate/long time, compressibility is expected to have a negligible impact on the solution …”
Section: Resultsmentioning
confidence: 99%
“…However, for the intermediate/long time, compressibility is expected to have a negligible impact on the solution. 52 The first comparison between laminar and turbulent flows is for the normalized opening. Figure 5 illustrates that the difference between normalized opening along the crack is relatively subtle; the scaled turbulent crack width is just slightly narrower.…”
Section: Comparison Between Turbulent and Laminar Solutionsmentioning
confidence: 99%
“…Different confining stresses are applied in three layers with the upper layer having a larger confining stress layer of 11 MPa, the lower layer having a confining stress of 5 MPa, and the layer in the middle (of 50 mm height) that contains the injection point having a confining stress of 7 MPa (see Figure ). The others parameters are as follows: E=3.9×1010Pa,KIc=0,CL=0,μ=30Pa·s,Qo=0.0023mL/s. Due to a rather large injection line, the effective injection rate entering the fracture varies with time due to fluid compressibility effects during the initial pressurization phase (see Lecampion et al for discussion). The evolution of the injection rate into the fracture can be approximated here by three constant injection steps: 0.0009 mL/s for the first 31 seconds, 0.0065 mL/s for the next 120 seconds, and 0.0023 mL/s for the rest of the experiment.…”
Section: Verification and Test Casesmentioning
confidence: 99%